Analyzing Early Reading Fluency of Second Graders through Words Correct Per Minute (WCPM) Method to Support Multiliteracy Development in Elementary Education - Nuraida, Elin (International Conference on Elementary Education, 2025)
This study examines the early reading fluency of second-grade students using the Words Correct Per Minute (WCPM) method as a diagnostic basis to support multiliteracy development in elementary education. The participants consisted of 87 students from four second-grade classes (2A–2D) at a public elementary school in Cimahi City. Data were collected through WCPM assessments,learning motivation questionnaires, and teacher interviews. Results showed that the average WCPM scores ranged from 59.13 (Class 2A) to 63.3 (Class 2C), indicating a moderate level of fluency across all classes. Motivation scores were also categorized as moderate (M = 50.74; SD = 25.84), suggesting that cognitive and affective aspects jointly influenced students’ reading performance. Interviews revealed that low reading fluency was affected by limited home literacy support, low confidence, and insufficient reading practice. These findings highlight the interrelation between cognitive, motivational, and environmental factors in early literacy development. The WCPM method proved effective in identifying students who require additional reading support. Overall, this study provides a diagnostic foundation for developing remedial literacy initiatives, such as the Reading Clinic based on the Seven BK Hebat Strategies, to strengthen reading fluency and multiliteracy in line with Sustainable Development Goal 4 on quality education.